If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5t + 1) + -4 = t + -1(t + 1) Reorder the terms: 2(1 + 5t) + -4 = t + -1(t + 1) (1 * 2 + 5t * 2) + -4 = t + -1(t + 1) (2 + 10t) + -4 = t + -1(t + 1) Reorder the terms: 2 + -4 + 10t = t + -1(t + 1) Combine like terms: 2 + -4 = -2 -2 + 10t = t + -1(t + 1) Reorder the terms: -2 + 10t = t + -1(1 + t) -2 + 10t = t + (1 * -1 + t * -1) -2 + 10t = t + (-1 + -1t) Reorder the terms: -2 + 10t = -1 + t + -1t Combine like terms: t + -1t = 0 -2 + 10t = -1 + 0 -2 + 10t = -1 Solving -2 + 10t = -1 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 10t = -1 + 2 Combine like terms: -2 + 2 = 0 0 + 10t = -1 + 2 10t = -1 + 2 Combine like terms: -1 + 2 = 1 10t = 1 Divide each side by '10'. t = 0.1 Simplifying t = 0.1
| .66+.23t=1.82t-.4 | | 10a+4=10a+4 | | -0.50x+10=14 | | -0.50x+10=0 | | (f-32).56=4 | | 25-[8-(5-11)]+(1-3)(1-3)(1-3)= | | 1.2+.6x=2.9+2.5x+.5 | | (5x-93)(7x+12)=0 | | 3(x-8)=46 | | (5x-93)(7x+12)=o | | 12y-8+16y-4=90 | | 12y-16y+8-14=90 | | 3/8=4x-2/12 | | 8+4(2b-3)=12 | | 3y=2.35-2x | | -6(5-2*x)=18 | | u^2+u-72=0 | | 15x+7=5x-8 | | 5(3z-1)-2(z+4)=8(z+1) | | 5/9*3= | | 52=-2s+3 | | 6.2x-1.5=4.7 | | .05z=20 | | 10-6=15 | | 200/228 | | 500=21x+20z | | X+16y=-25 | | 500=20x+21z | | x=2-0.5(2-0.5x) | | xsquared+9x=-15 | | 77=7(3a-1) | | 1/4t^3-16t |